Chemical modification of graphenes : synthesis and electrochemistry - Wong, Colin Hong An (2017)
Graphene has been touted as the next "wonder material" for various applications, owing to its excellent properties. The development of novel graphene materials enables hitherto unavailable characteristics for electrochemical applications, while in-depth and systematic study of graphene materials is necessary to understand its electrochemistry. Hence, new synthesis methods were explored using carbon nanotubes as a precursor to produce graphene materials, with analysis on the types of products formed and the effect of residual metallic impurities. A novel method for the reduction of graphene oxide nanoribbons was demonstrated to afford graphene nanoribbons with superior properties than those using conventional chemical reduction. The synthesis of graphene materials using rapid microwave treatment was also studied to provide insight on the influence of the precursor graphite oxide, with the procedure then being modified to successfully synthesize sulfur-doped materials that exhibited electrocatalytic activity. On the other hand, comprehensive investigations on current synthetic procedures were also conducted, revealing the impact of different methods on the levels of metallic impurity contamination of the graphene materials. The choice of graphite source was also shown to have varying, compounding effects on the properties of the resulting graphite oxides and graphene materials. Different techniques for the transfer of CVD graphene were compared in order to determine the most suitable method to obtain graphene films for electrochemical applications. These studies thus serve the dual purpose of expanding the synthetic toolbox available for graphene production as well as provide insight on the suitability of graphene materials for various electrochemical applications.